1999
DOI: 10.1124/mol.56.5.875
|View full text |Cite
|
Sign up to set email alerts
|

Binding Pockets of the β1- and β2-Adrenergic Receptors for Subtype-Selective Agonists

Abstract: We examined the subtype-selective binding site of the beta-adrenergic receptors (betaARs). The beta(1)/beta(2)-chimeric receptors showed the importance of the second and seventh transmembrane domains (TM2 and TM7) of the beta(2)AR for the binding of the beta(2)-selective agonists such as formoterol and procaterol. Alanine-substituted mutants of TM7 of the beta(2)AR showed that Tyr(308,) located at the top of TM7, mainly contributed to beta(2) selectivity. However, Tyr(308) interacted with formoterol and procat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
41
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 26 publications
8
41
0
Order By: Relevance
“…The mutation of Val-120 to Ala shows an indirect contribution to subtype selectivity of selected agonists (8). Although ligand binding was not affected in our study we also found that activation by terbutaline, but not by broxaterol, was changed by mutation of Val-120 to Leu in our case, confirming a significant role of this position.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The mutation of Val-120 to Ala shows an indirect contribution to subtype selectivity of selected agonists (8). Although ligand binding was not affected in our study we also found that activation by terbutaline, but not by broxaterol, was changed by mutation of Val-120 to Leu in our case, confirming a significant role of this position.…”
Section: Discussionsupporting
confidence: 75%
“…Isogaya et al (8) describe a number of mutations including mutation of Val-120, which is one of the positions that led to a gain-of-function mutation in our study. The mutation of Val-120 to Ala shows an indirect contribution to subtype selectivity of selected agonists (8).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As with our findings, these investigations reported that amino acid substitutions were introduced within transmembrane domains. Another investigation confirmed that replacement of eight amino acids of transmembrane domain 2 of the β 1 -AR had shown that this transmembrane domain is a major determinant of the highaffinity binding of the β 1 -AR selective agonists (28). However, an amino acid in the same domain was not considered in the present study.…”
Section: Discussionmentioning
confidence: 43%